Stars and gods - Niven, Larry (Tor, 2010)
"... collects a dazzling assortment of Niven's most eclectic work into one captivating volume. Here are hand-selected excerpts from his novels ... as well as numerous short stories, nonfiction articles, collaborations, and correspondence"--Jacket.